Analisis Citra Rumah Sakit Umum GMIM Bethesda Tomohon pada Unit Rawat Jalan Tahun 2020 - Patrick Muljono; Aaltje E. Manampiring; Fatimawali Fatimawali (Universitas Sam Ratulangi, 2023)
Abstract: Hospital image could affect the attitude and behaviour of patients towards the hospital. This study aimed to evaluate the relationship between the variables studied and the image of Rumah Sakit Umum GMIM Bethesda (RSUGB). This was a descriptive study with a cross sectional design. The independent variables in this study were familiarity, emotional aspect, service, environment, and finance. The dependent variable was the image of RSUGB. Data were statistically analyzed with the chi square test using the SPSS version 22 computer program. The results showed that most respondents (89.0%) felt that hospital familiarity was good; (68.2%) felt emotional towards a good hospital; (67.9%) felt that the service at the hospital was good; (87.2%) felt that the environment of the hospital was good; and (68.8%) felt that the financial rates at the hospital were good. The chi square test or cross tabulation of the five independent variables on the dependent variable indicated that only the service variable towards hospital image had a p-value < 0.05 (p=0.018). Other variables such as familiarity (p=0.166), emotional aspect (p=0.473), environment (p=0.057), and finance (p=0.200) had p-values >0.05. In conclusion, there is a relationship between service and the image of Rumah Sakit Umum GMIM Bethesda (RSUGB), however, there are no relationships between familiarity, emotional aspect, environment, and finance with the hospital image. Keywords: familiarity; emotional aspect; service; environment; finance; hospital image Abstrak: Citra sebuah rumah sakit berdampak pada sikap dan perilaku pasien terhadap rumah sakit tersebut. Penelitian ini bertujuan untuk mengetahui hubungan variabel yang diteliti dengan citra Rumah Sakit Umum GMIM Bethesda (RSUGB). Jenis penelitian ialah deskriptif dengan desain potong lintang. Variabel bebas ialah familiaritas, emosional, pelayanan, lingkungan dan keuangan sedangkan variabel terikat ialah citra RSUGB. Analisis data secara univariat dan bivariat menggunakan uji chi square dengan bantuan program komputer SPSS versi 22. Hasil penelitian menunjukkan sebagian besar responden (89,0%) merasa familiaritas rumah sakit baik; (68,2%) merasa emosional terhadap rumah sakit baik; (67,9%) merasa pelayanan pada rumah sakit baik; (87,2%) merasa lingkungan di rumah sakit baik; dan (68,8%) merasa tarif keuangan di rumah sakit baik. Pada uji chi square atau tabulasi silang dari kelima variabel bebas terhadap variabel terikat didapatkan hanya variabel pelayanan dengan citra rumah sakit nilai p<0,05 (p=0,018). Variabel lainnya seperti familiaritas (p=0,166), aspek emosional (p=0,473), lingkungan (p=0,057), dan keuangan (p=0,200) mendapatkan nilai p>0,05. Simpulan penelitian ini ialah terdapat hubungan antara pelayanan dengan citra Rumah Sakit Umum GMIM Bethesda (RSUGB) namun tidak terdapat hubungan antara familiaritas, aspek emosi, lingkungan dan keuangan dengan citra rumah sakit. Kata kunci: familiaritas; emosional; pelayanan; lingkungan; keuangan; citra rumah sakit